Effectiveness of bisphosphonates on bone mineral density in osteopenic postmenopausal women: A systematic review and network meta-analysis of randomized controlled trials. Issue 31 (6th August 2021) - Dong, Su-li; Jiao, Yongqiang; Yang, Hai-liang
Abstract: Background: Various bisphosphonate agents have been proven to be effective in preventing bone loss and fracture in osteopenic postmenopausal women. This study was designed to compare the effectiveness of various BPs on preventing the loss of bone mineral density (BMD) for postmenopausal women with osteopenia. Methods: PubMed, EMBASE, and Cochrane Central Register of Controlled Trials were screened up to identify randomized controlled trails comparing effectiveness of BPs or placebo on the BMD of postmenopausal women with osteopenia. Network meta-analysis and standard pair-wise meta-analyses were performed. The main outcomes include the percentage changes of 6-, 12-, 24-, and 36-month BMD at lumbar, total hip and femoral neck, and frequencies of new fractures and severe adverse events. Results: Fourteen randomized controlled trials were eligible, involving 11, 540 participants. No significant difference was presented among the available interventions for the 6-month BMD at 3 different sites, but the magnitudes of differences among the treatment regimens became gradually increased along with the extending of follow-up periods. Daily aledronate of more than 5 mg provided the maximal percentage increase on BMD of femoral neck and lumbar spine, while zoledronate provided maximal change on BMD of total hip, at different follow-up periods. This network meta-analysis also demonstrated similar frequencies of new clinical fractures and severe adverse events among different interventions. Conclusions: A ranking spectrum depicting the effectiveness on BMD percentage change following interventions with different bisphosphonate regimens was provided. Generally, regimens with zoledronate and aledronate were found to be the most effective interventions in the 3 sites at different end points. Abstract : Supplemental Digital Content is available in the text